A close relationship: Euwallacea fornicatus (Eichhoff, 1868) haplotype H22 (Coleoptera: Curculionidae: Scolytinae) and Ricinus communis L. (Euphorbiaceae) in Brazil - Soares, Nyeppson S.; Duarte, Leonardo S.; Araújo, Alexandre S.; Rainho, Hugo L.; Hickmann, Frederico; Aurélio, Mateus S. L.; Silveira-Neto, Sinval; Zucchi, Roberto A.; Savaris, Marcoandre (Entomological Communications, 2026)
Euwallacea fornicatus (Eichhoff, 1868) (Coleoptera: Curculionidae: Scolytinae), the polyphagous shot hole borer (PSHB), is native to Asia and it has been recorded in Argentina (2023), Brazil (2024), and recently in Uruguay and Türkiye (2025), among other regions of the world. We document, for the first time, E. fornicatus on castor bean, Ricinus communis L. (Euphorbiaceae), in Brazil, which also represents the first record on this host for South America. A molecular phylogenetic analysis of PSHB from castor bean across Brazil, based on mitochondrial gene cytochrome c oxidase subunit I (COI) sequences, revealed a single haplotype (H22) in South America. We recorded PSHB on castor bean in 28 municipalities from five Brazilian states. Our results highlight the importance of including R. communis in PSHB monitoring programs.